Profile of patients assisted by endodontics specialty at the center of dental specialties (CEO) of a medium-sized city in countryside of the state of Paraíba (Research, Society and Development, 2023)
Organization of public dental services in Brazil is a challenge, as poor distribution and low supply capacity have generated pent-up demand for oral health services, mostly for endodontic treatment. This is a quantitative, descriptive, exploratory and cross-sectional study, The aim of the study was to evaluate the flow and organization of endodontic care and the profile of users served by the Dental Specialties Center in a city in the interior of the state of Paraíba (PB). Universe consisted of 18,400 medical records, which correspond to the number of registered users, who have already been or are waiting for care by one of the specialties, the sample consisted of 249 medical records of patients undergoing endodontics. It was observed that most of the individuals attended were women between 26 and 40 years old, the most affected teeth were molars and premolars. Although results characterized access to the assistance offered and the profile of users, there was a lack of access to information due to records being incomplete, in addition, there was no information available in the municipality's regulatory system, to assess flow and repressed demand or enable a comparison of endodontic care performed in the last five years, to analyze whether there was an improvement in access to the service. It was concluded that there is a necessity for improvement in filling of medical records, in reference and counter-reference, adoption of protocols for planning directed flow through an epidemiological survey that expresses the real demand, as well as expanding offer of endodontics service.